2016
DOI: 10.1111/jdi.12571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a newly‐devised nutritional guide based on self‐efficacy for patients with type 2 diabetes in Japan over 2 years: 1‐year intervention and 1‐year follow‐up studies

Abstract: Aims/IntroductionWe devised a new system called “Educational Guidance” (E‐Guide) for nutritional education based on self‐efficacy. The present study aimed to examine the effects of E‐Guide use on glycemic control among patients with type 2 diabetes.Materials and MethodsWe carried out an interventional and observational study that included 74 patients with type 2 diabetes. The extent of glycemic control in the 39 patients who received guidance through the E‐Guide (E‐Guide group) was compared with that of 35 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Factor 2 was based on informational and instrumental support, which can be interpreted from the effects of self‐efficacy. A previous study reported that nutritional education based on self‐efficacy improved glycemic control and self‐care behavior among patients with T2DM in Japan (Yamamoto et al, 2017). Factors 3, 4, 5, and 6 were based on instrumental support.…”
Section: Discussionmentioning
confidence: 99%
“…Factor 2 was based on informational and instrumental support, which can be interpreted from the effects of self‐efficacy. A previous study reported that nutritional education based on self‐efficacy improved glycemic control and self‐care behavior among patients with T2DM in Japan (Yamamoto et al, 2017). Factors 3, 4, 5, and 6 were based on instrumental support.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, essa abordagem nutricional é demorada e, em muitos países, há poucos profissionais para atender adequadamente às demandas dos serviços (Segal et al, 2013). Observou-se que os níveis de HbA1c diminuem significativamente e são mantidos durante período de acompanhamento de um ano, quando a educação em diabetes inclui abordagem de empoderamento para o autocuidado, como automonitoramento e metas de ação (Yamamoto et al, 2017). Também se observou que esses níveis reduziram significativamente quanto maior a frequência da educação nutricional (Nakagawa et al, 2014).…”
Section: Discussionunclassified